Spotlight on VET : vocational education and training systems in Europe - (:unkn) unknown (Publications Office of the European Union, 2015)
"This anniversary publication presents a concise picture of essential features of VET in Europe. Reporting on and analysing vocational education and training (VET) has been a Cedefop core activity throughout its 40-year history. In cooperation with its Refernet partners, Cedefop publishes a 'Spotlight on VET' for each EU Member State, Iceland and Norway. Spotlights present essential VET features of all 30 countries using comparable system charts based on each country's VET programmes, rather than schools or institutions. This approach inevitably involved simplification and us of common terminology. The information presented in the system charts is therefore not exhaustive but aims to illustrate main differences and similarities between the 30 countries at a glance." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2 Europa; Berufsbildungssystem; Europa